Synchronous gravitational search algorithm vs asynchronous gravitational search algorithm: a statistical analysis - Abd Aziz, N.A.; Ibrahim, Z.; Nawawi, S.W.; Sudin, S.; Mubin, M.; Abd Aziz, K. (2014)
Gravitational search algorithm (GSA) is a new member of swarm intelligence algorithms. It stems from Newtonian law of gravity and motion. The performance of synchronous GSA (S-GSA) and asynchronous GSA (A-GSA) is studied here using statistical analysis. The agents in S-GSA are updated synchronously, where the whole population is updated after each member’s performance is evaluated. On the other hand, an agent in A-GSA is updated immediately after its performance evaluation. Hence an agent in A-GSA is updated without the need to synchronize with the entire population. Asynchronous update is more attractive from the perspective of parallelization. The results show that both implementations have similar performance.